Towards an understanding of the boundaries and characteristics of a Digital Business Strategy - Fredericks, Jeanne (Department of Information Systems, 2021)
The merging of business and information technology (IT) strategies, effectively becoming a Digital Business Strategy (DBS), is changing the way that organisations have to leverage resources to create differential value. Due to the DBS being such a novice idea, there is no clear understanding of what the DBS is, what its characteristics and boundaries are, how it impacts alignment between business and IT, and how it impacts organisational performance. Without this understanding, organisations leveraging a DBS run the risk of launching technological initiatives or making organisational changes that are disjointed from their strategic direction. These misaligned efforts may result in unrealised strategy and unsatisfactory organisational performance. The purpose of this study was to define the boundaries and characteristics of the DBS, provide a definition of a DBS and to establish if the DBS has a positive effect on organisational performance. To examine the DBS, it was observed in its natural habitat, through a single case study approach, focusing on an organisation that has been leveraging a DBS as part of their digital journey. The organisation is a South African based financial services provider and is a subsidiary of a larger financial services provider. In this study, the DBS was observed from an intellectual, operational, social and cultural alignment perspective, using a combination of the Strategic Alignment Model (SAM) and the Complex Adaptive System (CAS) frameworks. This study subscribed to a mixed-method approach which included both qualitative and quantitative research techniques. Staff providing input into this study included senior, middle, junior and non-management employees. The study was conducted over a period of thirteen months. The findings from both the qualitative and quantitative data suggest that to leverage a DBS the organisation must be concerned with more than just leveraging digital resources. For instance, organisations must focus on customer and staff empowerment, use customer and industry-related information to create opportunistic and competitive decision-making opportunities, and create a change-ready culture where bold experimentation and failing forward is embraced. Researchers and practitioners alike can use the findings of this case study as lessons on how to leverage organisational resources in the context of the DBS.